The Analysis of Speech Acts Found in The Text of Timun Emas - Juliarta, I Made; Wirawan, I Gede Nika (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study investigated the speech acts found in the text of Timun Emas. This research applied a deductive-inductive method in getting the data found in the Timun Emas texts. Data analysis aimed to get the information used as a basis for making decisions to solve a problem. The data analysis process in this research is stated as the process of grouping data according to its characteristics, creating a data grouping model and obtaining important information from the data in the text. In data analysis, this research analyzed the data in accordance with the theory used. They are analyzing the text of Timun Emas based on the types of speech acts and analyzed the social context found in the text of Timun Emas. The types of speech acts found in the text of Timus Emas are directive and commissive. It indicated that the giant had a bad intention to take Timun Emas. The findings reveal that the story predominantly contains directive and representative speech acts, reflecting the characters’ intentions to instruct, warn, and convey information. Commissive and expressive acts appear less frequently but play significant roles in expressing promises, gratitude, and emotional states. These results highlight the pragmatic richness of the folktale and its potential as a medium for teaching language functions in educational contexts.